Viçosa mixture in tomato cultivation as a potential strategy for crop development and insect pest repellency - Félis, Grazielly Santos; Assis, Franscinely Aparecida de; Carvalho, Fabio Janoni; Assis, Gleice Aparecida de (Revista de Ciências Agroveterinárias, 2025)
Viçosa misture is a modification of Bordeaux mixture, as it contains macro and micronutrients in its composition, which contribute to improving plant nutrition, favoring increased productivity. In addition, it repels phytophagous insects, helping with pest management. It can be used in organic farming, as long as it complies with the legislation governing this type of farming. Based on the above, the objective of this study was to evaluate the effect of spraying Viçosa mixture on agronomic development, repellency to insect pests, and incidence of natural enemies in tomato plants (Solanum lycopersicum L.). For this purpose, a randomized block design with five treatments (concentrations of Viçosa mixture) was used, as follows: T1 - 0 g L-1; T2 - 1 g L-1; T3 - 2 g L-1; T4 - 3 g L-1 and T5 - 4 g L-1, and five blocks, totaling 25 plots, each plot consisting of three pots, totaling 75 experimental units. Parameters related to tomato plants were evaluated, as well as the characterization of fruits and quality attributes of tomatoes, in addition to the population density of insect pests and the number of eggs of natural enemies. It was found that there was a significant difference between the concentrations of Viçosa mixture for some characteristics related to tomato plants and fruits. Positive correlations were also obtained between certain variables analyzed. As for phytophagous arthropods, there was repellency for insects with scraping-sucking, sucking, and chewing feeding habits as a result of the application of Viçosa mixture. In addition, a higher density of predatory insect eggs was obtained on plants sprayed with this mixture. Thus, it can be concluded that spraying with Viçosa mixture contributes to improving the agronomic aspects of tomato plants and repels insect pests, without negatively interfering with the oviposition of chrysopids.